Fertility Awareness and its Association with Socio-demographic and Reproductive Variables among Women Seeking Fertility Treatment: A Cross-sectional Study - Nisha Malik; Pooja Sinha; Smiti Nanda; Namita Batra; Vikram Singh; Ravishekar N Hiremath (Journal of Clinical and Diagnostic Research, 2022)
Introduction: In the last decade, there was a substantial reduction in fertility rates in Indian women. Despite a high burden of infertility, Fertility Awareness (FA) among people of reproductive age group is generally poor. Infertility is associated with significant negative impact on social and psychological well-being of the married couple. Therefore there is a need for awareness on fertility among Indian women. Aim: To assess the level of fertility awareness and determine the impact of socio-demographic and reproductive variables on FA among a cohort of Indian women seeking fertility treatment. Materials and Methods: A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Pandit Bhagwat Dayal Sharma Postgraduate Institute of Medical Sciences, Rohtak, Haryana, India, including 108 women seeking fertility treatment over a period of six months. Participants were interviewed with a 10 item questionnaire and categorised into low (score <40%), moderate (score 40-59%) or high FA level (score ≥60%) according to percentage of correct answers. The association of socio-demographic and fertility characteristics with FA levels was statistically analysed using Statistical Package for the Social Sciences (SPSS) software version 18.0. Results: Of the total 108 participants, majority (90.7%) of women were aged between 21-35 years and primary infertility (67.6%) was the most common type. The overall FA level was low in 27.8%, moderate in 44.4% and high in 27.8% study participants. Majority answered incorrectly about fertile period (60%) and age related fertility decline (55.6%). Nearly, two-thirds respondents believed that conception is not possible by any means if fallopian tubes are blocked. FA levels differed significantly between the age groups (p-value=0.001). The other socio-demographic and reproductive variables did not demonstrate any significant association with FA levels. Conclusion: Considerable gaps in knowledge and understanding of fertility issues were identified irrespective of their socio-demographic and fertility characteristics which warrant urgent attention. Targeted interventions are required to ensure easy to access accurate fertility information for couples’ informed decision making.